Ultrasensitive measurement of gas refractive index based on cascaded Mach–Zehnder interferometers and Vernier effect. (2nd June 2021) - Li, Jun; Cheng, Hongwei; Lin, Hongfeng; Li, Hao; Zhou, Ai
Abstract: An ultrasensitive gas refractive index (RI) sensor based on fiber Mach–Zehnder interferometers (MZIs) and Vernier effect is proposed and demonstrated. The sensor consists of two cascaded fiber MZIs, one of which serves as a reference unit and is fabricated by fusion splicing a section of symmetrical side-hole fiber in between two short pieces of multi-mode fiber (MMF); the other acts as a sensing unit, which is composed of a section of tapered single-mode fiber sandwiched between two sections of MMF. The two MZIs are designed to have similar free spectral range for generating optical Vernier effect. Because the two MZIs have different responses to external RI, the RI-related Vernier effect can be obtained and the RI sensitivity can be improved, while there is no temperature sensitivity enhancement because the two MZIs have the same response to temperature. Thus the structure has low temperature crosstalk when obtaining high RI sensitivity. Experimental results show that the gas RI sensor has an ultrahigh sensitivity of 4.2 × 10 4 nm RIU −1 (RI unit). At the same time, the temperature cross-sensitivity is only 2.2 × 10 −6 RIU °C −1 . Therefore, the proposed sensor has potential applications for modern gas concentration monitoring in a large dynamic range.